Methanogenic abundance and changes in community structure along a rice soil chronosequence from east China. (27th May 2016) - Liu, Y.; Wang, P.; Crowley, D.; Liu, X.; Chen, J.; Li, L.; Zheng, J.; Zhang, X.; Zheng, J.; Pan, G.
Summary: Changes in abundance, community structure and activity of archaea were investigated for rice paddy soil under long‐term cultivation along a chronosequence that spans 700 years in a coastal area of east China. Topsoil samples were analysed for archaeal abundance and community structures, which were determined with archaeal 16S rRNA and methanogenic mcrA genes. Methane production potential (MPP) was evaluated concurrently with a laboratory anaerobic incubation of treated topsoil samples. Gene abundance of archaea and methanogenic archaea increased from 6.70 × 10 6 and 1.53 × 10 5 copies g −1 in marsh to 2.89 × 10 8 and 2.73 × 10 7 copies g −1 in rice soil cultivated for seven centuries, respectively. Compared with the uncultivated marsh, diversity indices for both archaea and methanogenic archaea increased markedly with rice cultivation. Methanogenic archaeal community structure was dominated by Methanosarcinales and changed to a lesser extent after 100 years. The measured MPP varied over a range from 241.3 to 301.1 µg CH4  g −1 for the rice soil, whereas it was 101.3 µg CH4 g −1 for the uncultivated marsh soil. Therefore, gene abundance of both archaea and methanogenic archaea appeared to increase with the accumulation of organic matter following long‐term rice cultivation. The changes in MPP and community structure, however, were independent of differences in archaeal abundance. This suggests a complex interaction of soil organic matter, archaeal abundance and community structure, which could change the potential methanogenic activity in rice soil with long histories of rice cultivation. Highlights: How do archaeal and methanogenic archaeal communities change in response to long‐term rice cultivation? Improve understanding of archaeal communities and their function in rice soil over hundreds of years. Change in the archaeal community structure was controlled by soil desalinization and decalcification. Archaeal community diversity precedes soil morphological and mineralogical development.